Pengaruh Pembelajaran Berdiferensiasi Bermedia Serbaneka Terhadap Kemampuan Peserta Didik Menulis Teks Slogan Fase D SMP Perguruan Teladan Medan - Sihotang, Jontor Nados; Sitorus, Pontas J.; Panggabean, Sarma (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This research aims to determine the effect of differentiated learning using various media on students' writing ability to write slogan texts for Phase D Middle School at Teladan Medan College T.A.2023/2024. This type of research is quantitative experimental research with a two group posttest-only control design. Quantitative research is research that is based on calculating statistical figures in its findings. The population in this study were all class VIII students with a total of 64 students with the sample for this research being VIII-1 with 32 students and VIII-2 with 32 students determined using a simple random sampling technique. The data analysis technique used is the normality test, homogeneity test and hypothesis test. After conducting research for pretest and posttest experiments using Miscellaneous media, the average score for the control class was 61.56 with a standard deviation of 9.16 and the experimental class average was 81.25 with a standard deviation of 12.24. The pre-test and post-test data prerequisite test results stated that the sample had a normal and homogeneous distribution. From the results of testing the research hypothesis, a "t" test was carried out at a significant level of α= 0.05, obtained Tcount > Ttable = (7.1861 > 1.693). Thus the null hypothesis (Ho) is rejected and the hypothesis (Ha) is accepted. So it can be concluded that there is a significant influence on the use of various media at VIII Medan Model College Middle School T.P 2023/2024.